PERANAN UNIT BINAAN MASYARAKAT DAN FORUM KEMITRAAN PERPOLISIAN MASYARAKAT DALAM MENCEGAH TINDAK PIDANA RINGAN TAHUN 2015 DI WILAYAH HUKUM POLISI SEKTOR TAMPAN KOTA PEKANBARU BERDASARKAN PERATURAN KAPOLRI NOMOR 22 TAHUN 2010 TENTANG SUSUNAN ORGANISASI DAN TATA KERJA PADA TINGKAT KEPOLISIAN DAERAH - Azizi, Yunharadi M.; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The criminal act is an act or acts punishable by the law. The offenses occurred in the District Charming Pekanbaru includes theft, runaway underage girls, defamation and adultery. This was due to the minimal number of members of the Police Sector Tampan Pekanbaru City impacting not maximum performance of members of the police in preventing crime that happened. Therefore it takes an active part of society together with the police in preventing crime that happened. To then formed a forum called Community Policing Partnership Forum (FKPM). The purpose of this thesis, namely: First, to determine the effectiveness of the role of Patronage Society Unit and Community Policing Partnership Forum in preventing minor criminal offenses within the jurisdiction of the Police Sector Tampan Pekanbaru. Second, to determine the role of effort Patronage Society Unit and Community Policing Partnership Forum in preventing minor criminal offenses within the jurisdiction of the Police Sector Tampan Pekanbaru.This type of research can be classified in this type of sociological research. The research location is Tampan Pekanbaru Police Sector. Source data used are primary data and secondary data. Data collection techniques are interviews, questionnaires and review of the literature. After the collected data was then analyzed qualitatively using the deductive method of drawing conclusions from things that are common to the things that are special.From the research, there are two main things that can be inferred, first, Role Unit Patronage Society and Partnership Forum Community Policing in Preventing Crime in Jurisdiction Police Sector Tampan Pekanbaru city can be done by face to face and socialization, and their coordination in the government districts , municipality, police and the local community. Second, the effort to make the role of Patronage Society Unit and Community Policing Partnership Forum can prevent minor criminal offenses within the jurisdiction of the Police Sector Tampan Pekanbaru city can be done by good coordination among institutions, conduct education and socialization, active participation of the community.Keywords: Role - Unit Binmas - FKPM - Preventing - Criminal